The Effective Project Management Approach Towards Minimising Environmental Impacts in The Construction Industry - Ismail, Radzi; Othmani, Muhammad Izzat; Said, Ilias; Dan, Wang (UUM Press, 2023)
One factor in a nation’s successful economic growth and social well-being is the construction industry. Regrettably, the construction industry is also associated with a range of environmental impacts, including air pollution, noise pollution, soil contamination, and other related problems. The construction activities will have a detrimental environmental effect, significantly impacting the comfort and quality of life of individuals, particularly in urban regions like Klang Valey, Malaysia, where the pace of development is very rapid. However, project management approaches in construction projects can efficiently reduce adverse environmental impacts. Nevertheless, the adoption of project management approaches in construction projects, particularly in medium to small scale ones, remains significantly low. Although the use of project management has numerous advantages, it also presents significant hurdles for construction professionals in efficiently incorporating it into their professions, particularly in Klang Valley. Therefore, this research study aims to assess the level of comprehension among construction industry players in the Klang Valley regarding the environmental impact of construction activities. It also seeks to identify the challenges they face in implementing effective project management in construction projects and determine the most efficient approach to implement project management from the pre-construction stage to the post-construction stage, with the goal of minimising environmental impacts. Interviews were conducted with seven experienced experts who specialise in diverse construction projects. The findings indicated that they aware of the advantages, but they faced major hurdles in putting those advantages into action. Despite their awareness of the advantages, they were unable to successfully implement them.